Image Structure in Kurdish Romantic Poetry - Karim, D. Zayer Latif; ئەمین, د. عبد القادرمحەمەد (Sulaimani Journal for Humanities, 2001)
Any text consists of a number of images, each one gives a special meaning and when connected together they give more meanings , thus the text becomes more beautiful and effective. This Research depends on: A singal image (sensuous perceptions, which deals with senses, Simili and direct description). The absolute image (circular structure, logical structure and mythical structure. The romantic Kurdish poetic texts are applicable scopes in this research.